2006
DOI: 10.1071/zo06006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on the survival, growth and development of tadpoles of the brown tree frog, Litoria ewingii

Abstract: We investigated the effects of 4% seawater (sw), 8% sw, 12% sw and 16% sw (1.4 g NaCl L–1, 2.8 g NaCl L–1, 4.2 g NaCl L–1 and 5.6 g NaCl L–1, respectively) on survival, mass and development of larvae of the brown tree frog, Litoria ewingii. Salinity of 16% sw significantly decreased survival of tadpoles such that 39% of tadpoles in 16% sw treatment survived to metamorphosis compared with 92% in the control group (freshwater). Growth (mass) of 16% sw tadpoles (0.048 g ± 0.005 g) slowed significantly during earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 35 publications
13
92
1
1
Order By: Relevance
“…This result is concordant with an earlier study in which L. ewingii tadpoles were observed to be 'sluggish' under saline conditions (Chinathamby et al 2006). In anurans, exposure to salt is known to affect both muscles and nerves, leading to physiological adjustments and biochemical changes that are often energetically demanding (Dole et al 1994).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result is concordant with an earlier study in which L. ewingii tadpoles were observed to be 'sluggish' under saline conditions (Chinathamby et al 2006). In anurans, exposure to salt is known to affect both muscles and nerves, leading to physiological adjustments and biochemical changes that are often energetically demanding (Dole et al 1994).…”
Section: Discussionsupporting
confidence: 91%
“…The tadpoles in the saline treatment were maintained in 15% SW (equivalent to 5.25 g NaCl l K1 ). This is an environmentally meaningful concentration (Smith et al 2007) that falls below the lethal limit for the species (Chinathamby et al 2006). Water in both groups was prepared using Coralife Scientific Grade Marine Salt (ESU Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three concentrations of NaCl (Fisher Scientific, Certified for Biological Work) were created using deionized water: 1.4 g L-', 3.5 g L-', and 5.6 g L-I. These concentrations were similar to those used by Chinathamby et al (2006) and Sanzo and Hecnar (2006), and they were within the range observed in some freshwater habitats, Environment Canada 2001). Five replicates of each concentration were used, with each replicate container holding 400 mL of salt solution and five tadpoles pooled from multiple (> 5) egg masses.…”
Section: Effects Of Salinity On Survivorship Of Wood Frogmentioning
confidence: 99%